Waste management in Botswana: Towards a more sustainable environmental management - Otlogetswe, totolo, (Malaysian Journal of Science, 2004)
Botswana like most developing countries is faced with many challenges and opportunities that include chemical and waste management. When Botswana attained independence in 1966, we had a very small population with very small generation of biodegradable waste. As a result of rapid economic development, Botswana has started to produce some waste that is not biodegradable and has long residence time in the environment. Some of this waste include plastics, batteries, scrap metals, used oil, and waste paper, glass, medical/cljnical waste, old tyres among others. Medical/clinical waste has been a problem in Botswana more especially the transportation and disposal aspects. Clinical waste that has been identified compromise, biological waste, infectious waste, Sharps, Chemical waste, Body fluids/excreta, radioactive waste. Oil waste has resulted from various industrial activities that have been very difficult to store and reuse. Oil sales are projected to grow to 12.7 million litres by the year 2005 with a growing recovery of 6.34 million litres. Paper, glass and packaging waste continue to be a menace to our environment. 1996, it has been estimated that waste from paper was generated as follows: packaging material 18 600 tonnes, paper for writing and printing as7 100 tonnes and miscellaneous paper accounted for 13 000 tonnes. Paper recycling is at an infant stage in Botswana. Quantity of glass generated is about 93 tonnes per annum, Scrap metals are piled up on private premises, dumped in the bush, abandoned in the streets or brought to communal landfill sites, or individuals keeping such scrap metals in their backyards. It is estimated that by 2005, 832 600 tyres will be required vehicles and 306 000 will go to scrap. Accidental fires on tyres are a common occurrence around most landfills in Botswana. Botswana needs well-articulated environmental legislation to deal with the above environmental concerns in order to realise sustainable environmental management